Rarity and viability value of different type of ecosystem and plants species in tropical forest ecosystem of Bungoh Catchment, Sarawak, Malaysia - Abdul Manaf, Latifah; Noweg, Gabriel Tonga; Met, Les (Marsland Press, 2014)
Bungoh catchment is located in the southern part of Sarawak, Malaysia and south east of Kuching town and densely covered by tropical forests. A study was conducted to determine the rarity and viability values of plant species and also the rarity and viability values of the four different types of forest ecosystem of Bungoh Catchment. The four major forest ecosystems include the primary forest, old secondary forest, young secondary forest and agroforestry. The numbers of trees were recorded from the entire three different forest ecosystem using single plant method of size 400 square meters (20m X 20m). A total of 373 individual trees representing 148 species were recorded from the four different types of forest ecosystem. Out of 148 species, 22 species were recorded from the primary forest, 72 species were recorded from old secondary forest whereas 37 species were recorded from young secondary and the remaining 17 species were recorded from agroforestry. The rarity and viability value of plants species or ecosystem types is of immediate importance for the biodiversity conservation. The approach is designed for assessment of the rarity and viability values of plants species in the four major forest ecosystems in Bungoh Catchment. The rarity values are measured based on the frequency of certain plants species or ecosystems types are encountered whereas the viability value is assessed by considering three indicators which includes the core area, isolation and disturbances. The results indicate that the rarity value of all the four types of ecosystem namely the primary forest, old secondary forest, young secondary forest and agroforestry were relatively high indicating that the species in the ecosystem are distributed equitably and reflect the commonness of the species. Conversely, the viability value of the entire four ecosystems relatively low indicating that the species are prone to extinction.